Unidirectional Alleviation of the Diffraction Limit in Geometrically Anisotropic Photonics - El Badri Youssef; Mangach Hicham; Belkacem Abdelhaq; Oubeniz Hammou; Bouzid Abdenbi; Achaoui Younes (E3S Web of Conferences)
Rationally constructed materials have enabled access to optical capabilities beyond nature’s limitations, thanks to advances made in both theory and experiment. These synthetic composites allow subwavelength confinement of electromagnetic energy and facilitate unparalleled control over different aspects of electromagnetic waves (polarization, amplitude, frequency, etc.). However, the diffraction phenomenon is severely hindering the efficacy and performance of dielectric photonic components. Diffraction causes the electromagnetic wave to spread and deviate from its intended path, thereby, making the collimated light beam scatter, leading to lower power density and inaccurate targeting. This is particularly detrimental for applications requiring precise control of high-frequency with shorter wavelengths. Herein, we report on the effect of anisotropic geometrical scaling of dielectric photonic crystals to alleviate the diffraction barrier along the Γ → X path of the irreducible Brillouin region. Thus, achieving the long-sought goal of high-frequency electromagnetic wave steering. We harness the full weight of modal and harmonic analysis based on the Finite Element Method to demonstrate that scaling the direction perpendicular to the wave’s propagation reduced by fourfold the diffraction limit from 100 THz to 400 THz.